Enhancing Village Information Transparency and Economic Empowerment Through Website Management Training in West Bayah - Tri Wahyudi; Erlina Sari Pohan; Dwi Fitrianingsih; Gita Puspita (Alesha Media Digital, 2026)
Strengthening public information openness at the village level is crucial to promote transparency, accountability, and community participation. However, the use of village websites in many areas, including Bayah Barat Village in Lebak Regency, is still limited to static information and has not yet developed as an interactive public service medium. This situation is exacerbated by the limited digital literacy of village officials and inadequate internet infrastructure. This community service activity uses a participatory-based training and mentoring model with a learning by doing method. The stages of the activity include initiation, planning, technical training, mentoring, and post-training evaluation. The results show a significant increase in digital literacy among village officials, with the average skill score rising from 52% to 81%. The previously static village website now features activity news, financial reports, and promotion of local SMEs. Post-training evaluation also indicates an increase in public access to information and participation in village deliberations. Although internet infrastructure remains a barrier, this activity successfully demonstrated that a learning by doing approach with continuous evaluation can strengthen the capacity to manage village websites as a tool for public information openness and local economic empowerment.